2020
DOI: 10.21059/buletinpeternak.v44i4.56115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Inorganic Fertilizers on Yield and Quality of Synedrella nodiflora (Tropical Weed)

Abstract: This study aimed to determine the effect of organic and inorganic fertilizers on the cultivation of tropical weed Synedrella nodiflora as forage. The study was conducted from May to July 2018. The treatments of the research were control (C), organic fertilizer (D) and organic fertilizer + urea (DU), with 3 replications that were arranged on experimental design with a completely randomized design, in a unidirectional pattern and continued with least significant different (LSD). Organic fertilizer dosage in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Ingredients used in this study were rice bran, and Legetan that harvested from the pasture land of Forage Forage and Pasture Science Laboratory. dry matter (DM), 23% CP and 30% crude fiber (CF) [5], rice bran contains DM 89.2% DM, ash 13.8%, 8.6% CP, 10.8% ether extract (EE), CF 21.6%, and 45.33% nitrogen free extract (NFE) [7]. There were two (2) compositions of forage pellets, namely: A = 90% Legetan and 10% rice bran B = 80% Legetan and 20% rice bran…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ingredients used in this study were rice bran, and Legetan that harvested from the pasture land of Forage Forage and Pasture Science Laboratory. dry matter (DM), 23% CP and 30% crude fiber (CF) [5], rice bran contains DM 89.2% DM, ash 13.8%, 8.6% CP, 10.8% ether extract (EE), CF 21.6%, and 45.33% nitrogen free extract (NFE) [7]. There were two (2) compositions of forage pellets, namely: A = 90% Legetan and 10% rice bran B = 80% Legetan and 20% rice bran…”
Section: Methodsmentioning
confidence: 99%
“…People is looking for solution to maintain feed suplly in both season by feed technology processing [3]. Another side, Indonesia has abundant potential type of forage sources that can be used as feed for ruminant diet, weeds Legetan (Synedrella nodiflora) is one of it [4] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of Urochloa e.g. excellent adaptation to low-fertility acid soils were previously reported, compatible with the tropical climate, and tolerant to drought condition [1,2,3].…”
Section: Introductionmentioning
confidence: 93%
“…Incorporating high fiber such as paragis leaves into snack items may, therefore help achieve the recommended dietary fiber intake of these picky children. Paragis grass can contribute to about 21.57% to 29.17% of crude fiber (Garcia et al, 2003;Morah & Otuk, 2015;Suwignyo et al, 2017), to as high as 64% as reported by Jackson et al (1996), with digestibility coefficient of 69.6 (Regmi et al, 2004). Furthermore, macro and microminerals were reported present in paragis grass (Serra et al, 1997;Gbadamosi, 2012); among which are Co, Cu, Fe, Ca, K, Mg, Na, P. But incorporating grass in foods expectedly could impart undesirable taste and aftertaste in the product.…”
Section: Introductionmentioning
confidence: 99%